Advanced Techniques in Multimedia Watermarking : image, video, and audio applications - Mohammad Al-Haj, Ali (Information Science Reference, 2010)
"This book introduces readers to state-of-art research in multimedia watermarking in the different disciplines of watermarking, addressing the different aspects of advanced watermarking research; modeling and theoretical analysis, advanced embedding and extraction techniques, software and hardware implementations, and performance evaluations of watermarking systems"--Provided by publisher.